(untitled) (Journal of Educational Sciences, 2024)
Background: Kazakhstan, like all countries, aims to implement the 17 UN Sustainable Development Goals, in particular to support and provide education to the entire population. The aim of this study is to explore the role of Psychological-medical-pedagogical consultations (PMPC) and tools used to work with autism spectrum disorder (ASD) children. Methods: A questionnaire was developed for PMPC specialists based on 16 questions. The surveys were conducted using Google Forms. The results were analyzed using SPSS13. Additionally, an analysis was carried out to the open-ended questions that were coded to be statistically quantifiable. The thematic approach was used for qualitative data from the survey. Results: 346 respondents from eight regions of Kazakhstan took part in the survey. The majority of survey participants noted the growth of children with ASD and associate this fact with ecology, genetics and the development of digital technologies. Six categories as: socialization, communication, cognition, behavior, self-service skills as well as laws and standards were identified for placing a child with ASD to the regular school. A need was identified for advanced training of PMPC specialists to improve the provision of support to children with ASD and their caregivers. Keywords: Autism Spectrum Disorder, PMPC, Special Educational Needs, iclusive education, diagnosis.